2014
DOI: 10.1089/jwh.2014.4911
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex and Gender on Adaptation to Space: Behavioral Health

Abstract: This article is part of a larger body of work entitled, ''The Impact of Sex and Gender on Adaptation to Space.'' It was developed in response to a recommendation from the 2011 National Academy of Sciences Decadal Survey, ''Recapturing a Future for Space Exploration: Life and Physical Sciences for a New Era,'' which emphasized the need to fully understand sex and gender differences. In this article, our workgroup-consisting of expert scientists and clinicians from academia and the private sector-investigated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Moreover, the cardiovascular system is impacted by circadian rhythm and spaceflight leads to significant alterations in heart rate [ 156 , 157 ], blood pressure [ 158 ] and cardiovascular rhythms [ 159 ]. Similar observations have been made in animal models [ 160 , 161 , 162 ] and in human ground-based analogs such as the 520-d Mars mission [ 163 ]; and sex-based differences have been observed between astronauts [ 164 ]. Upon arrival on the Moon and Mars, astronauts will experience yet new light-dark cycles, and new ground-based models should now investigate the coupling effect of reduced loading and altered circadian rhythms to develop new and effective countermeasures.…”
Section: Outstanding Questionssupporting
confidence: 68%
“…Moreover, the cardiovascular system is impacted by circadian rhythm and spaceflight leads to significant alterations in heart rate [ 156 , 157 ], blood pressure [ 158 ] and cardiovascular rhythms [ 159 ]. Similar observations have been made in animal models [ 160 , 161 , 162 ] and in human ground-based analogs such as the 520-d Mars mission [ 163 ]; and sex-based differences have been observed between astronauts [ 164 ]. Upon arrival on the Moon and Mars, astronauts will experience yet new light-dark cycles, and new ground-based models should now investigate the coupling effect of reduced loading and altered circadian rhythms to develop new and effective countermeasures.…”
Section: Outstanding Questionssupporting
confidence: 68%
“…This assumption is corroborated by a study that suggested gender differences with a deteriorated sleep quality in women to be become apparent under the impression of anxiety and depression [ 66 ]. This difference between men and women may be important, when considering life and work, not only in polar research stations, but also during long-term missions in space [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The basal metabolic rate of both male and female decreased almost linearly with age after 20. However, between ages of 26 and 46, 41 the average ages for astronauts, the basal metabolism reduction was found to be moderate. 42 Finally, for the medical research, sometimes the sampling size is not so big, with statistical results supporting significant differences recorded.…”
Section: Discussionmentioning
confidence: 82%